Reactions of N,N′-bis(2-hydroxyethyl)oxalamide with Ethylene Carbonate and Use of the Obtained Products as Components of Polyurethanes Foams - Iwona Zarzyka-Niemiec (International Journal of Polymer Science)
N,N-bis(2-hydroxyethyl)oxalamide (BHEOA) was subject to hydroxyalkylation with ethylene carbonate (EC). By means of instrumental methods (IR, 1H-NMR, MALDI ToF, GC, and GC-MS), an influence of the reaction conditions on structure and compositions of the obtained products was investigated. The hydroxyalkyl and hydroxyalkoxy derivatives of oxalamide (OA) were obtained by reaction of BHEOA with 2–10-molar excess of ethylene carbonate (EC, 1,3-dioxolane-2-one). The products have a good thermal stability and possess suitable physical properties as substrates for foamed polyurethanes. The obtained products were used in manufacturing the rigid polyurethane foams which possess enhanced thermal stability and good mechanical properties.